Mznfe2o4 (M = Ni, Mn) Cubic Superparamagnetic Nanoparticles Obtained by Hydrothermal Synthesis - Casagrande-Denardin, J (2013)
MZnFe2O4 (M = Ni or Mn) cubic nanoparticles have been prepared by hydrothermal synthesis in mild conditions and short time without any procedure of calcinations. The structural and magnetic properties of the mixed ferrites were investigated by X-ray diffraction, Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, Mössbauer spectroscopy, vibrating sample magnetometer, and Transmission electron microscopy (TEM). X-ray analysis showed peaks characteristics of the spinel phase. The average diameter of the nanoparticles observed by TEM measurements was approximately between 4 and 10 nm. Spectroscopy study of the spinel structure was performed based on Group Theory. The predicted bands were observed in FTIR and Raman spectrum. The magnetic parameters and Mössbauer spectroscopy were measured at room temperature and superparamagnetic behavior was observed for mixed ferrites. This kind of nanoparticles can be used as precursor in drug delivery systems, magnetic hyperthermia, ferrofluids, or magnetic imaging contrast agents. © 2013 Springer Science+Business Media Dordrecht.